2007
DOI: 10.1074/jbc.m702526200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Small Ubiquitin-like Modifier-dependent Nuclear Import of the Thymidylate Biosynthesis Pathway

Abstract: Perturbations in folate-mediated one-carbon metabolism increase rates of uracil misincorporation into DNA during replication, impair cellular methylation reactions, and increase risk for neural tube defects and cancer. One-carbon metabolism is compromised by folate deficiency and common genetic polymorphisms. In this study, the mechanism for the preferential partitioning of cytoplasmic serine hydroxymethyltransferase (cSHMT)-derived methylenetetrahydrofolate to de novo thymidylate biosynthesis was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
136
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(141 citation statements)
references
References 60 publications
(68 reference statements)
5
136
0
Order By: Relevance
“…1). Nuclear thymidylate biosynthesis is enabled by the SUMO-dependent nuclear import of SHMT1 and TS (12,13). An increase in SUMOylation in response to UV treatment has previously been reported for several proteins involved in cellular stress response including TIP60 (41), xeroderma pigmentosum, complementation group C (42), and DJ-1 (43).…”
Section: The Expression Of Shmt1 Ismentioning
confidence: 99%
See 1 more Smart Citation
“…1). Nuclear thymidylate biosynthesis is enabled by the SUMO-dependent nuclear import of SHMT1 and TS (12,13). An increase in SUMOylation in response to UV treatment has previously been reported for several proteins involved in cellular stress response including TIP60 (41), xeroderma pigmentosum, complementation group C (42), and DJ-1 (43).…”
Section: The Expression Of Shmt1 Ismentioning
confidence: 99%
“…The concentration of free folate in the cell is negligible, and therefore, TS and methylene-THFR compete for limiting pools of the 5,10-methylene-THF cofactor (5)(6)(7)(8). Several studies have demonstrated that whereas the majority of 5,10-methylene-THF derived from the reduction of 10-formyl-THF is directed toward the synthesis of methionine (9, 10), SHMT1-derived 5,10-methylene-THF is partitioned to TS (11) through the cell cycle-dependent and small ubiquitin-like modifier (SUMO)-mediated nuclear localization of the thymidylate biosynthesis pathway (12,13) that enables the nuclear de novo synthesis of thymidylate (14) (Fig. 1).…”
mentioning
confidence: 99%
“…1) (1,2). Folate metabolism is compartmentalized in the cytoplasm, mitochondria, and the nucleus (2)(3)(4)(5). In the cytoplasm, folate-activated carbons are incorporated into the 2nd and 8th positions of the purine ring and are required for the conversion of uridylate to thymidylate and for the methylation of homocysteine to methionine.…”
mentioning
confidence: 99%
“…Tetrahydrofolates (THF) 3 are present in cells as a family of metabolic cofactors that carry and chemically activate single carbons for a network of biosynthetic pathways referred to as folate-mediated one-carbon metabolism ( Fig. 1) (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation